A Brand New Old Inscription Arad Ostracon 16 Rediscovered via Multispectral Imaging - Mendel-Geberovich, Anat; Finḳelshṭayn, Yiśraʾel 1949-; Cordonsky, Michael; Faigenbaum-Golovin, Shira; Piasetzky, Eli; Shaus, Arie; Sober, Barak (2017)
Arad Ostracon 16 is part of the Elyashiv Archive, dated to ca. 600 b.c. It was published as bearing an inscription on the recto only. New multispectral images of the ostracon have enabled us to reveal a hitherto invisible inscription on the verso, as well as additional letters, words, and complete lines on the recto. We present here the new images and offer our new reading and reinterpretation of the ostracon.
Keywords: Arad; Elyashiv Archive; Judah; Northwest Semitic epigraphy; Epistolography; Literacy; multispectral imaging; seventh century b.c